Science objectives of the magnetic field experiment onboard Aditya-L1 spacecraft - Yadav, Vipin K.; Srivastava, Nandita; Ghosh, S.S.; Srikar, P.T.; Subhalakshmi, Krishnamoorthy (My University, 2018)
The Aditya-L1 is first Indian solar mission scheduled to be placed in a halo orbit around the first Lagrangian point (L1) of Sun-Earth system in the year 2018–19. The approved scientific payloads onboard Aditya-L1 spacecraft includes a Fluxgate Digital Magnetometer (FGM) to measure the local magnetic field which is necessary to supplement the outcome of other scientific experiments onboard. The insitu vector magnetic field data at L1 is essential for better understanding of the data provided by the particle and plasma analysis experiments, onboard Aditya-L1 mission. Also, the dynamics of Coronal Mass Ejections (CMEs) can be better understood with the help of insitu magnetic field data at the L1 point region. This data will also serve as crucial input for the short lead-time space weather forecasting models. The proposed FGM is a dual range magnetic sensor on a 6 m long boom mounted on the Sun viewing panel deck and configured to deploy along the negative roll direction of the spacecraft. Two sets of sensors (tri-axial each) are proposed to be mounted, one at the tip of boom (6 m from the spacecraft) and other, midway (3 m from the spacecraft). The main science objective of this experiment is to measure the magnitude and nature of the interplanetary magnetic field (IMF) locally and to study the disturbed magnetic conditions and extreme solar events by detecting the CME from Sun as a transient event. The proposed secondary science objectives are to study the impact of interplanetary structures and shock solar wind interaction on geo-space environment and to detect low frequency plasma waves emanating from the solar corona at L1 point. This will provide a better understanding on how the Sun affects interplanetary space. In this paper, we shall give the main scientific objectives of the magnetic field experiment and brief technical details of the FGM onboard Aditya-1 spacecraft.
Keywords: Interplanetary magnetic field; Fluxgate magnetometer; Coronal mass ejection; Alfven waves; Geomagnetic pulsations; L-1 position satellite